Visage Of Feminist Discourse In Arundhati Roy’s Work: A Comparative Study Of Her “World’s Social Forum Speeches” And “The God Of Small Things” (Journal of Namibian Studies : History Politics Culture, 2022)
This research aims to analyze the purpose and genuine intention of Arundhati Roy in her work The God of Small Things and her "World Social Forum Speeches."  It also does a comparative analysis of the depiction of feminism in both works. Critical Discourse Analysis is an approach that investigates the connections between language and the socio-political aspects in which it is used. It explores issues like gender, politics, ethnicity, economy, and religion that are interlinked with the use of language in social settings. The present study does the critical discourse analysis of The God of Small Things and Roy's 'World Social Forum Speeches.' The results of this study are based on the CDA model of Van Dijk. Van Dijk's CDA primarily studies how social power abuse, dominance, and inequality are enacted, reproduced, and resisted by text and talk in socio-political contexts. The findings of this study reveal that Van Dijk's model is equally suitable to understand the writer's concept of feminism in her written and oral texts. The results of this research paper show how Arundhati Roy has come up with a different concept of feminism as she vehemently criticizes those modern actresses who do not want to use the tag of feminist for themselves but at the same time pretend to fight for their liberty and rights. The study also highlights the key similarities and differences between Roy's and other feminists' approaches to the concept. Toni Morrison has advocated for the rights of black women as in her society; women were treated as inferior not because of their gender but also for their race.On the other hand, Arundhati Roy indicates a double exploitation of women in Indian society, where they are marginalized racially and also on the basis of gender. Virginia Woolf advocated for the intellectual power of women. She says if we give women a separate room, she can provide us with brilliant artistic work. Likewise, Arundhati Roy is also fighting for women considered incapable of decision-making and wielding power. In addition, the results of this paper show how Arundhati Roy is advocating for women's rights through her writings and speeches by using different narrative techniques (being first person in her speeches and third person in her writings).In her speeches, she advocates for women's rights in the first person, and in her writings, she, as a third-person observer, comments on the plight of Indian women.